The Quivis Construction in Biblical Hebrew: History of a Syntactic Change - Samet, Nili (JAOS, 2023)
We discuss the evolution of the distributive double noun (quivis) in biblical Hebrew. This construction developed from an asyndeton in Classical Biblical Hebrew (e.g., איש איש) into a syndeton in Late Biblical Hebrew (e.g., איש ואיש), a process that makes it an important diachronic marker in classifying and analyzing these two varieties of the language .